#TITLE_ALTERNATIVE# - FITRIANI (NIM : 10309019); Pembimbing : Prof. Dr. Suryadi Siregar, DEA, PRATIWI
The observation of visual binary stars is not only measuring the angular separation between its components but also measuring the position-angle of its components depends on the respective epochs. The measurements can be derived in order to get values of orbital elements, determining masses and parallax. Thiele-Innes-Van den Bosch method can be used to determine the value of orbital elements of visual binary system. In this method, we choose three epoch positions as reference for determining orbital elements. We can also remodelled its geometry of orbit using those three epoch positions. Determining orbital elements of visual binary system needs an analytic and numerical studies, as well as manual modification of observation's data in order to fulfil Kepler's second law. Masses of each components, distance of the system, and approximation of age can be determined using Baize-Romani's Mass-Luminosity Relation. For visual binary star BSO 13AB which has an approximate period around one thousand years yet it only had been revolving nearly for a quarter of its orbit, it is given that Thiele-Innes-Van den Bosch method is not quite accurate to determine objectÃ‚Â’s orbital elements and to remodelled its orbit. The relatively high value of error may lower the confidence's percentage of the obtained result. Manual modification of observation's data also influences the result. Hence, we need to develop another method to determine Kepler constant in order to fulfil Kepler's second law.